Representation of Postcolonial Feminism in Noonari’s Black Bird in a White Cage - Sadam Hussain; Shafqat Hussain (ELITE JOURNAL, 2021)
The research attempts to depict Azhar Noonari’s work, Black Bird in a White Cage, and marginalization of women in Pakistani society. The research is carried out under the shed of postcolonial feminism. This idea is proposed by Gayatri Chakravorty Spivak in her essay, Can the Subaltern Speak. The study follows qualitative approach and Textual Analysis Method. Azhar Noonari has presented the ugly picture of male-dominated society particularly Pakistani society before and after its partition. The women of Pakistan have been suffering in every walk of their lives. They are not allowed to marry with their consent, they are compelled to serve their masters, and are being slaughtered in the name of honor and so on. This suggests the meaning that men in the postcolonial society of Pakistan are practicing their power to suppress women. Thus, women become an easy prey to their men and social taboos. So, the researcher has examined and deconstructed the plight of Pakistani women in the novel, Black Bird in a White Cage. Keywords: Postcolonial feminism, Subjugation, Postcolonial Pakistan